2009
DOI: 10.1002/qua.22076
|View full text |Cite
|
Sign up to set email alerts
|

On the interaction of rubidium and cesium mono‐, strontium and barium bi‐cations with DNA and RNA bases. A theoretical study

Abstract: ABSTRACT:We performed a density functional investigation of the interactions of the two alkaline metal ions Rb(I) and Cs(I) and two alkaline earth metal ions Ba(II) and Sr(II), with DNA and RNA nucleobases. All the possible molecular complexes, originated from the attack of these cations to the different binding sites present on some selected low-lying nucleobase tautomers, were considered to determine their relative stabilities and the preferred metal coordination geometries and sites. Absolute metal ions aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Most of these studies were focused on the interactions with singly-charged metal ions, both alkali metal ions and transition metal ions [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. More recently, many publications reported studies in which the metal ion interacting with the base is a doubly-charged species, in particular alkaline-earth metal dications [6,7,[15][16][17][18][19][20][21], but also transition metal dications such as Cu 2+ , Ni 2+ or Zn 2+ [7,11,22,23]. As a consequence, a lot of information has been gathered mainly on the structure of the corresponding complexes and on the effects of the metal ion on the geometry of the base or in its capacity to form pairs with other bases [7,15,22].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were focused on the interactions with singly-charged metal ions, both alkali metal ions and transition metal ions [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. More recently, many publications reported studies in which the metal ion interacting with the base is a doubly-charged species, in particular alkaline-earth metal dications [6,7,[15][16][17][18][19][20][21], but also transition metal dications such as Cu 2+ , Ni 2+ or Zn 2+ [7,11,22,23]. As a consequence, a lot of information has been gathered mainly on the structure of the corresponding complexes and on the effects of the metal ion on the geometry of the base or in its capacity to form pairs with other bases [7,15,22].…”
Section: Introductionmentioning
confidence: 99%
“…7). Both Sr(II) and Ba(II) cations complex with the O 2 sites of both U and T (Marino et al 2010). This same study found C1-Sr(II) and C1-Ba(II) complexes are the most stable and therefore most likely to bind these complexes to C mono-coordinated ions with O-M(II)-bond lengths of 2.302 and 2.442 A.…”
Section: Barium and Strontiummentioning
confidence: 63%
“…Overall, Rb(I) and Cs(I) display the highest affinity for G, with BP affinities in the order of G > C > T > U > A (Marino et al 2010). This trend is typical amongst alkaline earth metals, along with a general decrease in BP affinity with increasing atomic number (Zhu et al 2004).…”
Section: Rubidium and Caesiummentioning
confidence: 83%
See 2 more Smart Citations